2004
DOI: 10.1073/pnas.0405642101
|View full text |Cite
|
Sign up to set email alerts
|

Delayed neuropathology after carbon monoxide poisoning is immune-mediated

Abstract: The neuropathological sequelae of carbon monoxide (CO) poisoning cannot be explained by hypoxic stress alone. CO poisoning also causes adduct formation between myelin basic protein (MBP) and malonylaldehyde, a reactive product of lipid peroxidation, resulting in an immunological cascade. MBP loses its normal cationic characteristics, and antibody recognition of MBP is altered. Immunohistochemical evidence of degraded MBP occurs in brain over days, along with influx of macrophages and CD-4 lymphocytes. Lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
169
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 36 publications
8
169
0
11
Order By: Relevance
“…Protein bands identified as containing biotin on Western blots were cut from nitrocellulose paper, trypsin-digested, and analyzed with a nano-liquid chromatography/nanospray/LTQ mass spectrometer following our published methods (36). The raw data files were searched using Mascot against the NCBI data base with a cutoff protein score of 70.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein bands identified as containing biotin on Western blots were cut from nitrocellulose paper, trypsin-digested, and analyzed with a nano-liquid chromatography/nanospray/LTQ mass spectrometer following our published methods (36). The raw data files were searched using Mascot against the NCBI data base with a cutoff protein score of 70.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants were discarded and pellets resuspended in SDS buffer for Western blots that were probed with anti-biotin following published methods (36). Band densities were quantified using an Odyssey Infrared Imager (Li-Cor, Inc., Lincoln, NE).…”
Section: Methodsmentioning
confidence: 99%
“…Thom et al showed a decrease in inflammatory markers in the brain after HBO therapy with improved performance on maze testing [9][10][11][12][13]. Meanwhile, Gilmer et al showed no benefit from one treatment in terms of cognitive outcome [14], but this study was subsequently criticized for excessive hypoxic insult to the animals, which may have inadvertently obscured a potential benefit to HBO therapy [15].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Gilmer et al showed no benefit from one treatment in terms of cognitive outcome [14], but this study was subsequently criticized for excessive hypoxic insult to the animals, which may have inadvertently obscured a potential benefit to HBO therapy [15]. We sought to investigate whether three sessions of HBO would provide any benefit over a single treatment with HBO in preventing cognitive impairment in a murine model, using a previously established protocol [9,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Our poisoning protocol was based upon a previously published protocol demonstrated to induce delayed neurologic sequelae in mice [1]. This has been validated in additional studies [2][3][4], so we believe that our model was appropriate.…”
mentioning
confidence: 99%